Manajemen Pelayanan Ibadah Haji pada Lanjut Usia di Kementerian Agama Kabupaten Kaur - Hellen Oktarina Sari; Fatimah Yunus; Yunida Een Fryanti (STAI Terpadu Yogyakarta, 2022)
This paper aims to find out the hajj service for elderly congregations at the Kaur Regency Ministry of Religious Affairs office and to find out what are the obstacles in the Kaur Regency Ministry of Religious Affairs office in providing services to elderly congregations. This research uses a type of field research with a qualitative approach. The results showed that the management of hajj services at the Ministry of Religious Affairs of Kaur Regency was carried out properly. this is evidenced by the fulfillment of five indicators proposed by Zeithaml, namely Tangible; Reliability (reliability); Responsiveness; Assurance; and Empathy (empathy). The obstacles experienced by the ministry of religious affairs in Kaur district are the absence of Islamic bank institutions or muamalat, no KBIH institutions, siskohat networks, lack of human resources in the PHU section and education and health factors of elderly pilgrims.